Genomic profiling of interferon signaling pathway gene mutations in type 2 diabetic individuals with COVID-19 - Tuluk Tuncay; Kankılıç Teoman; Civelek İlkay; Akın Dilara Fatma; Bankır Mehmet (Türk Biyokimya Dergisi)
Comorbidities, especially diabetes, significantly contribute to the mortality and morbidity of COVID-19. Studies indicate higher rates of mortality and morbidity among diabetic COVID-19 patients compared to the general population. However, the precise mechanisms underlying this immune response remain incompletely understood. Our study aimed to explore potential disparities in COVID-19 prognosis among type 2 diabetic patients and investigate the genomic-level relationship between key proteins of the interferon signaling pathway: IFNAR1, IFNAR2, IRF3, and IRF7.